Digital Teaching Readiness among Islamic Education Students: The Role of Competence, Self-Regulation, and Media Use - Melly Nuryani; Taufik Hidayat (Al-Qalam Institue, 2026)
This study aims to examine the influence of digital competence and learning regulation on digital teaching readiness through digital media utilization among preservice teachers in an Islamic teacher education program. A quantitative explanatory design was employed, involving 50 undergraduate students selected through a saturated sampling technique. Data were collected using closed-ended Likert-scale questionnaires and analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings indicate that digital competence and learning regulation positively and significantly influence digital media utilization. Digital competence also has a positive and significant direct effect on digital teaching readiness, whereas learning regulation does not show a significant direct effect. Furthermore, digital media utilization significantly enhances digital teaching readiness but does not significantly mediate the relationships between digital competence, learning regulation, and digital teaching readiness. The structural model explains 26.6% of the variance in digital media utilization and 43.2% of the variance in digital teaching readiness. These findings imply that teacher education programs should prioritize strengthening students’ digital competence and expanding meaningful digital media utilization to better prepare future teachers for effective digital teaching in contemporary educational environments.